OPINIONS ON THE EMERGENCE OF THE KARLUK-KARAKHAN STATE - Makhmudov Bekhzod Khamidovich (Western European Studies, 2025)
This article is devoted to the question of when and on what date the state of QarluqKarakhons was founded. Mainly, existing conflicting and conflicting information in the science related to the initial period of the state, i.e., the date of its establishment, was compared and thoroughly analyzed.
Keywords: Qarluq; Karakhanlar; Chigil